2019
DOI: 10.1186/s12879-019-4498-x
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical characteristics in blood stream infections caused by Klebsiella pneumoniae, Klebsiella variicola, and Klebsiella quasipneumoniae: a comparative study, Japan, 2014–2017

Abstract: BackgroundKlebsiella variicola and K. quasipneumoniae are new species distinguishable from K. pneumoniae but they are often misidentified as K. pneumoniae in clinical settings. Several reports have demonstrated the possibility that the virulence factors and clinical features differ among these three phylogroups. In this study, we aimed to clarify whether there were differences in clinical and bacterial features between the three phylogroups isolated from patients with bloodstream infections (BSIs) in Japan.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 51 publications
(48 reference statements)
8
42
1
Order By: Relevance
“…While K. quasipneumoniae subsp. similipneumoniae has been less widely reported and discussed than K. pneumoniae, similar to our investigation, there has been an increased recognition of K. quasipneumoniae subspecies in hospital surveys and their association with resistance genes [57,58], indicating that a comprehensive assessment of their role in AMR ecology and contribution to disease burden is required. Their underrecognition is also due to the mis-assignment of non-K. pneumoniae strains to the type species.…”
Section: Discussionsupporting
confidence: 83%
“…While K. quasipneumoniae subsp. similipneumoniae has been less widely reported and discussed than K. pneumoniae, similar to our investigation, there has been an increased recognition of K. quasipneumoniae subspecies in hospital surveys and their association with resistance genes [57,58], indicating that a comprehensive assessment of their role in AMR ecology and contribution to disease burden is required. Their underrecognition is also due to the mis-assignment of non-K. pneumoniae strains to the type species.…”
Section: Discussionsupporting
confidence: 83%
“…Due to the high heterogeneity of K. pneumoniae, it often becomes difficult to determine the virulence factors of this species [7]. Nevertheless, the capsule of K. pneumoniae is one such virulence factor, and hypervirulence has been associated with differences in the expression of genes involved in the capsule, or with modified capsule phenotypes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Imai and colleagues recently reported that among 119 isolates obtained from patients with blood stream infection conventionally identified as K. pneumoniae, 21 isolates (17.7 %) were in fact K.variicola on further molecular analysis, five of which were ESBL-producers. However, there were no significant differences in clinical features, including 30-day mortality between the organisms [16]. In a recent study, Potter and colleagues reported pathogenicity of K. variicola in a murine model ofurinary tract infection [17].…”
Section: Discussionmentioning
confidence: 98%